Analysis of Prepaid Electricity Service Marketing Strategy PT. PLN ULP kalasan - Yumna Ibnu Ramadan; Anas Hidayat; Nur Azizah Basyirah (Cita konsultindo, 2024)
This research examines the marketing strategy for prepaid electricity service products implemented by PT. PLN ULP Kalasan, as well as evaluating its implementation and impact on energy use efficiency and customer satisfaction. The results of the analysis show that the implementation of the electrical energy saving program has succeeded in increasing the efficiency of energy use. However, there are still several supporting and inhibiting factors in the prepaid electricity program. Positive impacts on energy usage efficiency include better usage control, reduced energy waste, and awareness of electrical energy consumption. However, there are also negative impacts such as a potential decrease in revenue for the company. However, customer satisfaction analysis shows that prepaid electricity service products have succeeded in meeting customer expectations and needs. In conclusion, PT. PLN ULP Kalasan needs to continue to strengthen education and outreach efforts, innovate in offering attractive promotions and continue to monitor and evaluate the implementation of their marketing strategy regularly to increase effectiveness and efficiency in providing prepaid electricity services.